Pembinaan Olahraga Futsal Usia 11-16 Tahun di Club Female Football Project Kota Batu - Herlina Dwi Agestin; Febrilia Putri Mulyanti; Rhania Rizkika Dewayan; Merin Yunika Adelia; Yulingga Nanda Hanief (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Futsal coaching in East Java may still be lacking compared to other regions, but this can be overcome if futsal coaching in each club pays more attention to and improves upon all the factors that can influence or hinder the coaching process. However, the Female Football Project club in Batu city is experiencing problems in coaching girls' futsal, especially in fostering the 11-16 age category. This is caused by many factors such as training schedules, training motivation, motor movements each individual has and the availability of few coaches. The purpose of this activity is to make observations and analyzes regarding the success of fostering futsal sports in East Java. The method used is the MBKM Internship community service activities for 4-5 months. The results of the observations and analysis obtained, there are still many things that need to be improved in futsal coaching at the Female Football Project club, especially in dealing with the problem of decreasing training motivation in athletes because basic futsal skills development will not work well when training motivation in athletes decreases and of course more needs to be done. pay attention to sports psychology in order to pay more attention to the mental health of athletes because it will affect the achievements of athletes and clubs.